Influence of self-healing property of Ultra-High Performance Concrete under aggressive environment - Xi Bin; Ferrara Liberato (MATEC Web of Conferences, 2023)
This paper investigates the evolution of self-healing properties of ultra-high performance concrete exposed to aggressive environments. Double edge wedge splitting UHPC specimens with 0.8% crystalline admixture and 1.5% steel fibre by volume have been first pre-cracked up to a average 0.30 mm crack opening displacement (COD) obtained by two linear variable differential transformers attached to both sides of the sample surface. Then, the pre-cracked samples have been exposed to three different environments: tap water, salt water (a NaCl aqueous solution at 3.3% concentration) and geothermal water obtained from a geothermal power plant. After one month exposure, samples were carried out re-crack to know the self-healing properties. The results from ultrasonic pulse velocity tests (UPV) reveal that the samples exposed to tap water exhibit the highest rate of recovery along the exposure time, while those exposed to geothermal water show the lowest. The calculated indexes of cracking self-healing (ICS) show a 73.8% closure in tap water, 58.4% in salt water 43.9% in geothermal water. Additionally, the index of damage recovery, evaluated from UPV frequencies as well as from the stress vs. COD curves of pre-cracking and post-healing re-cracking tests on specimens, and the equivalent tensile stress also indicate a higher level of healing capable of inducing a significant recovery of mechanical properties.